Modelling and simulation of two competition slalom techniques - Supej, M.; Kugovnik, O.; Nemec, B. (Kinesiology, 2004)
The new geometry of skis highly affects skiing and consequently the slalom technique. A new improved slalom technique with a single movement has been recently presented. This study deals with the biomechanical modelling and computer simulation of the new technique and the old technique with double movement. The simulation is set to enable a comparison of forces and force distributions. It was found that the behaviour of the force is of vital importance because of the skier`s movement. Due to the movement, the force causes an increase and decrease in the total ground reaction force. The consequence of the different movements is a higher presence of the highest and strongest ground reaction forces acting in skiing when the double movement technique is applied. Furthermore, a much better steering of the skis can be achieved as a consequence of better contact with the snow, especially during the transfer of weight using the single movement technique. In addition to that, much lower knee momentums act around the gate in the single movement technique as a result of a more stretched body position. The final conclusion relating to the forces point of view achieved with computer simulation is that the new technique with a single movement is much more appropriate for the new skis. The conclusion is consistent with the measurement of forces and times presented in previous articles.